Avaliação do reprocessamento de copolímero SAN através de moldagem por injeção - Breda, Alcides (2011)
The main objective of this work was to study the reprocessing of copolymer SAN through injection molding and its influence on the mechanical, thermomechanical and optical behavior of that copolymer. Mechanical properties, measured by tensile and impact testing, and thermomechanical testing, measured through heat deflection temperature HDT and VICAT softening temperature were evaluated. In addition, yellowness index and optical properties, such as clarity and transparency, were observed for virgin SAN resin and its mixture with reprocessed SAN through injection molding in the form of cup of blender for 5 molding cycles. It was observed that the behavior of the reprocessed material has not shown significant changes through tensile, impact, HDT, and clarity properties. However, the VICAT softening temperatures and yellowness indices of the mixtures have suffered changes related to the SAN virgin grade. The chemical structure of multiprocessed SAN analyzed for FTIR has not shown significant changes, but the number average molecular weight of the copolymer has decreased, as verified by SEC. An increase in the MFI also has indicated chains scission.